ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI MODEL LEARNING CYCLE 7E DI SEKOLAH MENENGAH: learning cycle 7e: berpikir kritis: studi literatur - Sri Agustini Dalimunthe; Darta Darta; Thesa Kandaga; Vevi Hermawan (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2020)
This research is a qualitative research that provides information about mathematics learning in junior and senior high schools with the 7e learning cycle learning model for critical thinking skills. The purpose of this research is to describe critical thinking skills through the 7e learning cycle model. Data analysis techniques use deductive techniques, inductive techniques, and interpretation techniques. The results showed that Learning Cycle 7E learning model at the junior high school level, the indicator determining action was the largest and the lowest indicator was focusing on questions. In the high school level the interpretation indicator was the largest while the lowest was analysis indicators.